Analysis of the risk factors relating to cows' resistance to Rhipicephalus microplus ticks during the peripartum - Silva, Jenevaldo Barbosa da [UNESP]; Rangel, Charles Passos; Baeta, Bruna de Azevedo; Fonseca, Adivaldo Henrique da (Springer, 2014)
This study aimed to evaluate season, breed, number of lactations and milk production as risk factors relating to Rhipicephalus microplus infestation in dairy cows during the peripartum. Eighty-four animals were randomly selected through proportional stratified sampling. All engorged and partially engorged female R. microplus specimens measuring 4.5-8.0 mm were counted during the 5 weeks before calving, calving week and 5 weeks after calving. The peripartum had a significant effect [calving (p < 0.05; prevalence ratio (PR)= 3.12) and post calving (p < 0.05; PR = 2.02)] on R. microplus infestation. Although the average tick count was higher during the rainy season than during the dry season, there was no significant difference (p = 0.055; PR = 0.63). The average R. microplus count was significantly higher (p < 0.05; PR = 2.10) in Bos taurus animals, followed by F1 (p < 0.05; PR = 1.64) and Girolando (p < 0.05; PR = 1.39). The average R. microplus count was significantly higher (p < 0.05; PR = 0.97) in first-lactation animals, followed by those at the second, third and, fourth or subsequent lactation. Milk production showed a negative correlation with R. microplus count, such that high-production animals were significantly (p = 0.003; PR = 2.04) more vulnerable to infestation than were low-production animals. First-lactation and high-production B. taurus animals had greatest vulnerability to R. microplus infestation over the peripartum period, and constituted the at-risk group in the dairy herd.u
Keywords: Dairy cow; Lactation; Peripartum; Pregnancy; Ticks